Alkylated, naphthalimide-containing ionic compounds with rich thermotropic behaviour and nonlinear optical response. Issue 8 (26th January 2022) - Zhang, Geping; Lu, Dandan; Yin, Keyang; Godbert, Nicolas; Dong, Renhao; Li, Hongguang; Hao, Jingcheng
Abstract : Alkylated, naphthalimide-containing ionic compounds show rich phase transitions governed by the type (branched or linear) and length of the aliphatic chains. In film state, these compounds exhibit both third- and second-order nonlinear optical responses. Abstract : Chemical functionalization of π-conjugated units plays a key role in fine tuning their supramolecular organizations and functions. Herein, five 1, 8-naphthalimide derivatives were prepared where the naphthalimide moiety was attached to the imidazolium ring through a propyl linker. On the other side, the imidazolium ring was modified with either a branched aliphatic chain of 2-ethyl-hexyl (C2 C6, 1 ), 2-hexyl-decyl (C6 C10, 2 ) and 2-decyl-tetradecyl (C10 C14, 3 ), or a linear aliphatic chain of octyl (C8, 1′ ) and hexadecyl (C16, 2′ ). Temperature-dependent structural evolution of these alkylated, naphthalimide-modified imidazolium bromides (abbreviated to a-NaphImiBrs hereafter) were investigated in detail by differential scanning calorimetry and small-angle X-ray scattering measurements as well as polarized optical microscopy observations. The compound with the shortest branched aliphatic chain (1 ) self-organized into a columnar oblique (Colo ) phase at room temperature, which changed to a columnar rectangular (Colr ) phase upon heating. In comparison, its counterpart with a linear aliphatic chain of the same carbon number (1′ ) formed a crystal at room temperature, which shifted to a Colo phase at elevated temperature. The compound with a medium branched aliphatic chain (2 ) showed a columnar hexagonal (Colh ) organization at room temperature, which changed to a smectic (Sm) phase upon heating. Compounds with longer aliphatic chains (2′, 3 ), regardless of whether branched or linear, only exhibit the Sm phase. Films of a -NaphImiBrs formed at room temperature were subjected to evaluations for their nonlinear optical (NLO) responses where reverse saturated absorption was observed in all the cases. It was found that 2 showed the best NLO response with a third order nonlinear absorption coefficient of up to 0.49 cm W −1 .